Implementation of Public Health Insurance Policy Through the Sehati Program - Dady Miradi; Lukman Samboteng; Firdaus Firdaus (International Journal Labs, 2026)
The implementation of policies in the referral health system is one of the key components in efforts to realize tiered and integrated health services. The referral service policy in Belitung district has begun to be implemented in 2008 by issuing Belitung Regent Regulation Number 7 of 2008 concerning Belitung Public Health Insurance with a focus on providing health insurance to the people of Belitung, both those who have not been included in the Health Insurance borne by the government and the private sector. This policy was then updated several times last time by issuing Regent Regulation number 98 of 2022 concerning Belitung Public Health Insurance by covering all Belitung people who have not received health insurance through the JKN program in the form of contributions paid by the district government to BPJS Kesehatan as residents registered by the Belitung Regency Government. This research has a formulation of problems (1) the form of policy carried out by local governments in overcoming health services, especially referrals outside the region, (2) efforts that can be made in realizing an integrated referral service system, (3) the ways carried out by local governments in handling obstacles arising from the referral process. The research method used is in the form of a qualitative method with root cause analysis through in-depth interviews. The data sources used are primary and secondary data with a research focus containing statements about indicators and factors to be studied in detail.